Effect of obesity on alveolar bone loss in experimental periodontitis in Wistar rats - VERZELETTI, Giliano Nicolini (Faculdade de Odontologia de Bauru da Universidade de São Paulo, 2012)
Obesity has been linked to higher inflammatory status and periodontal breakdown. OBJECTIVE: The purpose of this study was to investigate the effect of obesity on alveolar bone loss in experimental periodontitis in rats. MATERIAL AND METHODS: Twenty-four female Wistar rats were randomly divided into two groups: obese (n=13), which were fed with "cafeteria diet" (CAF diet - high amounts of sucrose and fat) for 90 days in order to gain weight, and non-obese (n=11) regularly fed rats. Ligature-induced experimental periodontitis was created in all animals. Body weight differed statistically between obese and non-obese groups (277.59 and 223.35 g, respectively) at the moment of the ligature placement. Morphometric registration of alveolar bone loss was carried out after 30 days of ligature placement to determine the effect of obesity on the progression of experimental periodontitis. RESULTS: Intra-group comparisons showed significantly higher alveolar bone loss mean values in maxillary teeth with ligature (P<0.05). Alveolar bone loss [mean (SD), mm] was not statistically different between obese and non-obese groups [0.71 (0.09) and 0.65 (0.07) mm, respectively]. However, when palatal sides are analyzed separately, obese group presented significantly higher alveolar bone loss (P<0.05) as compared to non-obese [0.68 (0.12) and 0.53 (0.13) mm, respectively]. CONCLUSIONS: In spite of the weak differences, it is possible to conclude that the progression of alveolar bone loss in ligature-induced periodontitis can be potentially influenced by body weight in rats.